Antimicrobial and antibiofilm activities of Cu(II) Schiff base complexes against methicillin-susceptible and resistant Staphylococcus aureus - Pooi Yin Chung; Ranon Earn Yueh Khoo; Hui Shan Liew; May Lee Low (BMC, 2021)
Abstract Background Methicillin-resistance S. aureus (MRSA) possesses the ability to resist multiple antibiotics and form biofilm. Currently, vancomycin remains the last drug of choice for treatment of MRSA infection. The emergence of vancomycin-resistant S. aureus (VRSA) has necessitated the development of new therapeutic agents against MRSA. In this study, the antimicrobial and antibiofilm activities of two copper-complexes derived from Schiff base (SBDs) were tested individually, and in combination with oxacillin (OXA) and vancomycin (VAN) against reference strains methicillin-susceptible and methicillin-resistant Staphylococcus aureus. The toxicity of the SBDs was also evaluated on a non-cancerous mammalian cell line. Methods The antimicrobial activity was tested against the planktonic S. aureus cells using the microdilution broth assay, while the antibiofilm activity were evaluated using the crystal violet and resazurin assays. The cytotoxicity of the SBDs was assessed on MRC5 (normal lung tissue), using the MTT assay. Results The individual SBDs showed significant reduction of biomass and metabolic activity in both S. aureus strains. Combinations of the SBDs with OXA and VAN were mainly additive against the planktonic cells and cells in the biofilm. Both the compounds showed moderate toxicity against the MRC5 cell line. The selectivity index suggested that the compounds were more cytotoxic to S. aureus than the normal cells. Conclusion Both the SBD compounds demonstrated promising antimicrobial and antibiofilm activities and have the potential to be further developed as an antimicrobial agent against infections caused by MRSA.